-7x-2y=11

Simple and best practice solution for -7x-2y=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-2y=11 equation:


Simplifying
-7x + -2y = 11

Solving
-7x + -2y = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
-7x + -2y + 2y = 11 + 2y

Combine like terms: -2y + 2y = 0
-7x + 0 = 11 + 2y
-7x = 11 + 2y

Divide each side by '-7'.
x = -1.571428571 + -0.2857142857y

Simplifying
x = -1.571428571 + -0.2857142857y

See similar equations:

| -9+x=14 | | -8x-4=16 | | 3n^2-12n+9=0 | | 8+5x=42 | | j+(-7)=-1 | | 4*2/3-1 | | p-(-7)=-2 | | 3x+99=-2x-1 | | 81m^4+106m^2+25=0 | | (-10)+m=(-2) | | -5x+68=-7x+8-3x | | 5.5=10em-5 | | -17+x=-12 | | r-5=-1 | | 3x+77=-6x-4 | | m-5=12-9+1 | | -3+y=19 | | 0=16t^2+8t+15 | | -12x-17=-13x+7+9x | | -10x^2-27xy-5y^2=0 | | 7x^2-56x-21=0 | | 0.02(60)+0.04x=0.03(50+x) | | -5x^2+6x+6=0 | | k-3=24 | | -x^2+2x-8=0 | | a+2(4+2a-c)-4c+2=0 | | v+9=U | | 5(7x-3)=-10(-2x+1) | | -6+27+(-70)= | | 5r^2=35r | | 5(f-8)=-40 | | 3x+12=28-5x |

Equations solver categories